Los efectos jurídicos de la resolución nº. NAC-DGERCGC16-00000204, frente a los convenios para evitar doble imposición suscritos por Ecuador - Ortiz Arias, Edgar David (2017)
In order to prevent the uniqueness of double taxation, States have established mechanisms to avoid the concurrence of fiscal sovereignty, in which case the taxpayer or taxable person bears the same taxation on the part of two States. In this context where the so-called double taxation agreements arise. Ecuador, as it could not be otherwise, has so far signed sixteen double taxation agreements with different countries, thus preventing, among subscribing States, the same income can be imposed on the same taxpayer in the same fiscal period. However, with the issuance of Resolution No. NAC-DGERCGC16-00000204, dated June 14, 2016, a problem arises through its application, since maximum amounts and requirements were established so that the automatic application of the benefits provided for in the Double taxation subscribed by Ecuador, which rule that in cases where the amounts exceed the limits set, the benefit of the agreements will be made through the return of taxes, which obviously affects the content of treaties. In this sense, throughout this paper an analysis will be made of the importance of the international double taxation agreements signed by Ecuador, which, having been legally concluded and being in the current status of our legislation, enjoy greater prerogatives against Resolution No. NAC-DGERCGC16-00000204 dated June 14, 2016, which is addressed in this study. The incompatibility of the resolution under investigation with respect to the contents of the double taxation agreements signed by Ecuador will be demonstrated; Which has as a consequence an undoubted effect on the right to legal certainty, established in the Constitution of the Republic.